Early-Onset Frontotemporal Dementia-Related Semantic Variant of Primary Progressive Aphasia: Multimodal Evaluation With Brain Perfusion SPECT, SPECT/MRI Coregistration, and MRI Volumetry. (12th March 2022) - Tsiouris, Spyridon; Bougias, Charalampos; Konitsiotis, Spyridon; Papadopoulos, Athanasios; Fotopoulos, Andreas
Abstract: Frontotemporal dementia (FTD) is a neurodegenerative disorder characterized by cortical and subcortical atrophies, with early involvement of the hippocampus and amygdala. A 58-year-old man with clinical presentation of primary progressive aphasia—particularly its svPPA (semantic variant)—and bilateral asymmetric (left-predominant) anterior temporal lobe atrophy on MRI was referred for brain perfusion SPECT. This revealed bilateral hypoperfusion of the anterior temporal lobe (sustained by software-fused SPECT/MRI), pointing toward FTD rather than Alzheimer disease. Furthermore, voxel-based MRI volumetric analysis confirmed bilateral atrophy affecting the hippocampus and amygdala. Combining SPECT with MRI was supportive of the early-onset FTD-related svPPA diagnosis.